Studi Historiografi tentang Dakwah Walisongo di Jawa dalam Buku Fakta Baru Walisongo Karya Zainal Abidin Bin Syamsuddin serta Buku Walisongo Glora Dakwah dan Jihad di Tanah Jawa (1404-1482) Karya Rachmad Abdullah - Resa Rahmanita; Etmi Hardi (Galanggang Sejarah, 2021)
This study examines the walisongo da'wah contained in the Walisongo New Fact Book by Zainal Abidin Bin Syamsuddin and the Walisongo Book of Da'wah and Jihad in the Land of Java (1404-1482), by Rachmad Abdullah. These two books describe Walisongo's da'wah in Java in a different form from the mystical and ma'rifat that the Javanese people have believed so far. The purpose of this study is to describe Walisongo's da'wah in Java in the book Walisongo New Facts by Zainal Abidin Bin Syamsuddin and Walisongo Glora's Book of Da'wah and Jihad in Java (1404-1482), by Rachmad Abdullah. This research is a library research, where this research limits itself to collection materials from the library without conducting field research (interview data). The approach used is a historical qualitative approach using content analysis methods. The conclusion obtained from this study is that the Walisongo da'wah described in these two books was obtained from the same source so that they have the same point of view and background in understanding Islamic studies in the beliefs held by the same Islamic group.Keywords: walisongo, da'wah, background.